The concept of "tourism sector" in the public system - Stepanov, V. (ХДАК, 2023)
The concept of “tourism sector” allows us to understand the social processes that take place in the field of tourism activities in the social system. To do this, we should consider the interpretation of the concept of “sphere”, which is studied both at the socio-philosophical and sociological levels.
Keywords: туризм; tourism